2021
DOI: 10.1002/mds.28838
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Magnetic Resonance Imaging Detects Progression in Parkinson's Disease: A Placebo‐Controlled Trial of Rasagiline

Abstract: Background Rasagiline has received attention as a potential disease‐modifying therapy for Parkinson's disease (PD). Whether rasagiline is disease modifying remains in question. Objective The main objective of this study was to determine whether rasagiline has disease‐modifying effects in PD over 1 year. Secondarily we evaluated two diffusion magnetic resonance imaging pulse sequences to determine the best sequence to measure disease progression. Methods This prospective, randomized, double‐blind, placebo‐contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The substantia nigra has a critical role in modulating motor movement and reward functions as part of the basal ganglia circuitry, and substantia nigra degeneration is the involved in the motor deficits observed in PD (Hodge & Butcher, 1980;Purves et al, 2001). Measurements of free water in the pSN have emerge as a reliable objective marker of disease progression in PD (Arpin et al, 2022). Our finding provides initial evidence that low-cost, video-based movement measures are linearly related to well-establish objective markers of disease progression in PD.…”
Section: Correlation With Mds-updrs III Item 4 Scorementioning
confidence: 52%
See 2 more Smart Citations
“…The substantia nigra has a critical role in modulating motor movement and reward functions as part of the basal ganglia circuitry, and substantia nigra degeneration is the involved in the motor deficits observed in PD (Hodge & Butcher, 1980;Purves et al, 2001). Measurements of free water in the pSN have emerge as a reliable objective marker of disease progression in PD (Arpin et al, 2022). Our finding provides initial evidence that low-cost, video-based movement measures are linearly related to well-establish objective markers of disease progression in PD.…”
Section: Correlation With Mds-updrs III Item 4 Scorementioning
confidence: 52%
“…This study employed clinical, imaging, and video data collected as a part of a previously completed clinical trial (Arpin et al, 2022). Table 1 summarizes the demographic information for the individuals selected for this study.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, rasagiline has been widely recognized for its neuroprotective effects 49 ; a previous retrospective study showed that PD patients with a history of rasagiline use had lower free water values in the PSN than those who had not chronically taken this medication 24 . Another randomized controlled study 25 found a four times greater increase in pSN free water in PD randomized to placebo compared to PD randomized to rasagiline. However, we did not find any differences between patients treated with and without MAO‐B inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Free water values in the ASN and PSN were compared across the four groups using analysis of covariance, adjusting for age, sex, and education. To understand whether MAO‐B (monoamine oxidase inhibitor‐B) treatment affects SN free water, 25 we divided the mPD group based on whether they had chronically used MAO‐B and compared the two groups. The relationship between clinical outcomes and PSN free water values in the pPD, dnPD, and mPD groups was investigated using multivariable linear regression analysis, controlling for age, sex, and education in pPD patients and these three variables in addition to disease duration in dnPD and mPD patients.…”
Section: Methodsmentioning
confidence: 99%